2010
DOI: 10.1074/jbc.m109.082305
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Compounds Parthenolide and Bay 11-7082 Are Direct Inhibitors of the Inflammasome

Abstract: Activation of the inflammasome generates the pro-inflammatory cytokines interleukin-1␤ and -18, which are important mediators of inflammation. Abnormal activation of the inflammasome leads to many inflammatory diseases, including gout, silicosis, neurodegeneration, and genetically inherited periodic fever syndromes. Therefore, identification of small molecule inhibitors that target the inflammasome is an important step toward developing effective therapeutics for the treatment of inflammation. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
434
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(474 citation statements)
references
References 46 publications
15
434
1
7
Order By: Relevance
“…We used ELISA to measure the level of IL-1␤ in the culture supernatant as a readout for NLRP3 inflammasome activation. The compound Bay 11-7082 inhibited Nlrp3 inflammasome activation in accordance with a previous report (22). We identified an additional chemical compound, MNS, that consistently abolished IL-1␤ secretion in our screening experiments (Fig.…”
Section: Identification Of Mns As a Potent Inhibitor For Atp-inducedsupporting
confidence: 75%
See 1 more Smart Citation
“…We used ELISA to measure the level of IL-1␤ in the culture supernatant as a readout for NLRP3 inflammasome activation. The compound Bay 11-7082 inhibited Nlrp3 inflammasome activation in accordance with a previous report (22). We identified an additional chemical compound, MNS, that consistently abolished IL-1␤ secretion in our screening experiments (Fig.…”
Section: Identification Of Mns As a Potent Inhibitor For Atp-inducedsupporting
confidence: 75%
“…6H). Bay 11-7082 has been reported to inhibit the ATPase activity of NLRP3 possibly through the mechanism of cysteine modification (22). We (Fig.…”
Section: Mns Prevents Nlrp3 Agonist-induced Asc Speck Formation Withomentioning
confidence: 79%
“…It has been reported that TAK1 is involved in NLRP3 inflammasome activation in an NF-B activity-dependent manner to facilitate classical NLRP3 agonist stimulation (23) or hypotonic stress-induced cell volume change (24). However, although Bay11-7082 is an inhibitor of the NF-B pathway, this compound has recently been proposed as a direct NLRP3 inhibitor independent of the NF-B pathway (25). Therefore, how TAK1 is involved in NLRP3 inflammasome activation remains unclear.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the presence of cathepsin B in the cytosol is an indicator of the extent of disruption of endosomes [29,30]. To examine the amount of cathepsin B released from endosomes to the cytosol, the plasma membrane was made permeable by a digitonin treatment.…”
Section: High Potency Of Endosome Disruption By Ysk12-mendmentioning
confidence: 99%